Pengembangan produk tempe tinggi zat besi dan protein dengan substitusi tepung hati ayam dalam upaya perbaikan anemia defisiensi besi - Ma'arif, Mohammad Zainul; Renowening, Yuniars; Mahmudah, Himmatunnisak (UHAMKA PRESS, 2024)
Iron deficiency can interfere with the formation of hemoglobin, causing iron deficiency anemia. If iron deficiency anemia continues during pregnancy, it can increase the risk of giving birth to a baby with stunting and anemia. This study aimed to develop a food product high in iron and protein by substituting chicken liver flour with soybean tempeh to produce a tempeh product that can be used as an alternative food to improve iron deficiency anemia. This study used a completely randomized design. The treatment in this study consisted of four levels of chicken liver flour substitution (F1=5%, F2=10%, F3=15%, and F4=20%) in making tempeh. Hedonic quality test data were statistically analyzed using the Mann–Whitney test. The data on iron level using the Atomic Absorption Spectrophotometry (AAS) method and protein level using the Kjeldahl method were statistically analyzed using the one-way ANOVA test and continued with the Tamhanes test. The results of this research show that the substitution of chicken liver flour produces products with iron and protein levels at the level of 10% (1.330 mg/100 g; 18.76 g/100 g), 15% (5.355 mg/100 g; 21.36 g/100 g) and 20% (3.089 mg/100 g; 25.31 g/100 g) respectively which were higher than the control group (p<0.05). The highest iron levels were obtained in group F3 with an iron level of 5.355 mg/100, and the highest protein levels were obtained in group F4 with a protein level of 21.36 g/100 g. Based on the hedonic quality test, the substitution of chicken liver flour reduced the quality of tempeh in several parameters, namely non-white color, pungent aroma, and tasteless taste typical of tempeh, compared to the control group (p<0.05). The substitution of chicken liver flour with concentrations of 10%, 15%, and 20% can increase iron and protein levels in tempe products.